Health-Related Quality of Life in Craniofacial Conditions: Concordance Between Child and Parent Reports. (May 2020) - Morgan, Austin; Ataseven, Burçin; Din, Hena; Blum, Jessica; Paap, Michael; Meier, Annie; Carrizosa, Claudia; Malcarne, Vanessa; Gosman, Amanda
Abstract : Introduction: Craniofacial conditions (CFCs) profoundly influence health-related quality of life (HRQoL). In children with CFCs, patient-reported outcome measures have become an integral adjunct to more objective surgical outcome measures. Patient-reported outcome measures are designed to assess HRQoL domains. Few studies have evaluated parent and child agreement about HRQoL in the context of CFCs. The aims of this study were to explore the impact of CFCs on HRQoL domains in children and their parents and to determine whether patient and parent perspectives converge. Methods: The Craniofacial Conditions Quality of Life Scale (CFC-QoL) is a newly developed 5-domain survey available in child self-report and parent report and in English- and Spanish-language versions. The 5 domains are the following: social impact, psychological function, physical function, family impact, and appearance impact. Children with CFCs (ages 7–21 years) and parents of children with CFCs were recruited via the craniofacial care team clinic at a major metropolitan children's hospital. All children and parents completed the CFC-QoL Scale in their preferred language of English or Spanish. Scale internal consistencies were calculated for child patients and parents, for English and Spanish versions. Scores on the 5 domains were compared for children and parents across English versus Spanish versions. Results: For children with CFCs (N = 75), the sex was distributed almost equally. Patients were mostly Hispanic (69.3%), and their ages ranged from 7 to 21 years old (M = 13.2, SD = 3.62). The mean values for patient and parent scores were low, suggesting good HRQoL across all 5 domains. Pearson correlation coefficients were computed to explore the interrelationships between patient and parent report for each of the 5 CFC-QoL subscales. For the total sample, patient and parent scores were significantly and moderately positively correlated for all subscales. When analyzed separately based on sex, ethnicity, and diagnostic group, the correlation patterns were not identical to those found for the total sample. When analyzed separately for diagnostic group, there was less consistency in patterns, with patient-parent dyads showing different levels of agreement based on child's diagnostic grouping. Conclusions: Although there is substantial agreement between parents and patients when considered on a group level, there is moderate agreement between patients and parents when considered at the dyadic level, underscoring the importance of measuring and considering both perspectives.